The Influence of Teacher Education Level and Working Period on Teacher Pedagogic Competence - Maryani, Maryani; Arafat, Yasir; Setiawan, Andi Arif (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this quantitative study is to investigate the effect of both partial and simultaneous differences in education level and tenure of service on teachers' pedagogical competence. A questionnaire was used to collect data for this study, and SPSS was used to analyze the data statistically. The study's findings suggest that the level of education and years of service have a partial or simultaneous influence on a teacher's pedagogical competence. This study makes recommendations for increasing teachers' educational levels in order to improve their pedagogical competence.